"Aggrecanase" activity is implicated in tumour necrosis factor alpha mediated cartilage aggrecan breakdown but is not detected by an in vitro assay. Issue 3 (June 1997) - Buttle, D J; Fowles, A; Ilic, M Z; Handley, C J
Abstract : AIMS: To develop an in vitro assay for the putative glutamyl endopeptidase, "aggrecanase", which is thought to degrade cartilage aggrecan, and to examine the role of the enzyme in tumour necrosis factor stimulated aggrecan cleavage. METHODS: Aggrecan fragments released by bovine nasal cartilage explants, with and without exposure to tumour necrosis factor alpha, were purified and analysed by western blotting and N-terminal sequencing. Intact bovine aggrecan was incubated with extracts of cartilage, lysed chondrocytes, or cartilage explant conditioned culture medium under a variety of conditions. Deglycosylated aggrecan was incubated with nasal cartilage explants. Proteoglycan breakdown was assessed by metachromatic assay of fragments in culture media, and cleavage of the substrate at the aggrecanase cleavage site was detected and measured using the antibody BC3, which recognises a neoepitope produced by aggrecanase cleavage of aggrecan. RESULTS: Aggrecan fragments generated from explants treated with tumour necrosis factor had N-terminal sequences consistent with cleavage of aggrecan at a restricted number of glutamyl bonds. Aggrecanase generated fragments were found in cartilage explant culture medium and chondrocyte monolayers. However, no aggrecanase activity could be detected in extracts of cartilage, or chondrocytes from which endogenous aggrecan fragments had been removed, under a variety of assay conditions. Deglycosylated aggrecan, added to explant cultures, efficiently inhibited endogenous aggrecan breakdown. CONCLUSIONS: Aggrecanase is active in cartilage and in chondrocyte monolayers, and its action is stimulated by tumour necrosis factor alpha. However, activity due to this enzyme could not be detected in vitro under our assay conditions, although a deglycosylated version of the substrate inhibited aggrecan breakdown in explant cultures.